2013
DOI: 10.1136/bmjopen-2013-003900
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with being overweight among Inner Mongolia medical students in China

Abstract: ObjectivesA major goal of our study was to identify the associations between lifestyle factors and obesity in adolescents and young adults at risk by surveying students in Inner Mongolia Medical University. A second goal was to determine these factors differed by gender.DesignCross-sectional study.SettingStudents grade 1–3 in Inner Mongolia Medical University.Participants5471 grade 1–3 medical students, composed of 3891 female and 1580 male students. Students with body mass index (BMI) ≥25 were defined as over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
11
1
3
Order By: Relevance
“…The prevalence of normal weight is consistent with previous studies carried out throughout the world, ranging from 49.2% to 58.3% [13,21,23]; but not for the prevalence of malnutrition categories. The present study, with 32.5% subjects being overweight and obese, marked a relatively higher rate when compared to the medical students in China (7.6%) [24] and Carolina (32.1%) [23]; however, the malnutrition status in the current study subjects was lower than those in Pakistan (41.7%) [21]. Comparing with local studies for these BMI categories, 35% was found in the medical students from AIMST university, Malaysia [13] and 57.1% was documented in adults with a similar age group (20-24) from a local nationwide health survey [11].…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…The prevalence of normal weight is consistent with previous studies carried out throughout the world, ranging from 49.2% to 58.3% [13,21,23]; but not for the prevalence of malnutrition categories. The present study, with 32.5% subjects being overweight and obese, marked a relatively higher rate when compared to the medical students in China (7.6%) [24] and Carolina (32.1%) [23]; however, the malnutrition status in the current study subjects was lower than those in Pakistan (41.7%) [21]. Comparing with local studies for these BMI categories, 35% was found in the medical students from AIMST university, Malaysia [13] and 57.1% was documented in adults with a similar age group (20-24) from a local nationwide health survey [11].…”
Section: Discussioncontrasting
confidence: 46%
“…This finding may also be due to the fact that there is a body image-exercise association which is used as a motivation for men to obtain a muscular physique [27]. Besides that, reduced physical fitness was found in women, in terms of speed, vital capacity and endurance, when compared to that of men [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Inner Mongolian adult's generally follow static activities in their daily life. Chen et al have investigated the obesity rate of Inner Mongolia adults and the study found that 13% of Inner Mongolia's men and women were obese, and the annual rate of increase was higher than the national average growth rate of 10.2% [5]. Otgontuya et al has pointed out that the increase in the rate of obesity in Inner Mongolia and its resident's lifestyle and customs have a great relationship [6].…”
Section: The Present Situation Of Physical Activities Of Mongolian Admentioning
confidence: 99%
“…Studies suggest that youth in rural area are more likely than youth in urban area to begin drinking at an early age and to engage in binge and heavy drinking and driving while intoxicated [10] [11]. The different between rural and urban area was also performed in some other aspects in Inner Mongolian medical university, such as breakfast consumption [12], overweight [13] and distress [14]. Therefore, furthermore to study the difference in alcohol use for urban and rural.…”
Section: Introductionmentioning
confidence: 99%